2020
DOI: 10.1038/s41598-020-60564-8
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene sequencing reveals an altered composition of the gut microbiota in chickens infected with a nephropathogenic infectious bronchitis virus

Abstract: Infectious bronchitis virus (IBV), a member of the Coronaviridae family, causes serious losses to the poultry industry. Intestinal microbiota play an important role in chicken health and contribute to the defence against colonization by invading pathogens. The aim of this study was to investigate the link between the intestinal microbiome and nephropathogenic IBV (NIBV) infection. Initially, chickenswere randomly distributed into 2 groups: the normal group (INC) and the infected group (IIBV). The ilea were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…The microbial dysbiosis in broilers can be linked to antibiotic resistance. Moreover, the association of microbial dysbiosis with antibiotic resistance in poultry could be supported by a previous study linking the predominance of Proteobacteria with microbial dysbiosis in ilea of nephropathogenic infectious bronchitis virus-infected chickens [48]. The over dominance of various pathobionts (E. coli, Klebsiella pneumonia, Salmonella enterica, Shigella flexneri) in this study is supported by the fact that an increased abundance of Proteobacteria has been linked with the emergence of pathogenic microbes [49,50].…”
Section: Discussionsupporting
confidence: 81%
“…The microbial dysbiosis in broilers can be linked to antibiotic resistance. Moreover, the association of microbial dysbiosis with antibiotic resistance in poultry could be supported by a previous study linking the predominance of Proteobacteria with microbial dysbiosis in ilea of nephropathogenic infectious bronchitis virus-infected chickens [48]. The over dominance of various pathobionts (E. coli, Klebsiella pneumonia, Salmonella enterica, Shigella flexneri) in this study is supported by the fact that an increased abundance of Proteobacteria has been linked with the emergence of pathogenic microbes [49,50].…”
Section: Discussionsupporting
confidence: 81%
“…We then investigated the associations between the caecal microbiota composition and immune phenotypes of the challenged animals in the total population and in the V-Ch and NV-Ch groups separately. A recent study reported the effect of nephropathogenic IBV (NIBV) infection on the ileal microbiota of Hy-Line brown chickens 33 . It was observed that NIBV disturbed the intestinal epithelium, with an hyperplasia of goblet cells, and a lowered ratio of the villus height to crypt depth.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the GreenGene database and MUSCLE software (version 3.8.31) were used to annotate the taxonomic information and conduct the multiple sequence alignment, respectively [44]. The alpha diversity index (Chao1, ACE, Shannon, Simpson indices), the beta diversity index, PCoA, NMDS and ANOSIM were conducted as previously described [45].…”
Section: Analysis Of Microbial Diversitymentioning
confidence: 99%